TEACHING CHARACTER EDUCATION THROUGH PLOT ANALYSIS IN GUY MAUPASSANT’S THE STORY OF A FARM GIRL - Eva Agustina Rahma Eva Agustina Rahma; Elisabeth Ngestirosa Endang Woro Kasih (Universitas Teknokrat Indonesia, 2023)
The aim of this research is to integrate character education by comprehending the plot in Guy Maupassant's The Story of a Farm Girl. Through an analysis and discussion of the novel's narrative, it becomes evident that the story follows a progressive plot structure. The stages, commencing with exposition and culminating in resolution, vividly illustrate this progression. In the exposition phase, characters and impending conflicts are introduced, while rising tensions materialize as Jacques breaks his promise to Rose upon discovering her pregnancy, subsequently fleeing. As Rose's pregnancy becomes conspicuous, her fears escalate, prompting her to remain hidden until childbirth. Although Rose weds her master, he remains unaware of her child. Ultimately, Rose reveals her concealed truths to Mr. Valin. Employing a descriptive analysis methodology, this research underscores the implications of plot analysis in The Story of a Farm Girl for character education in schools. It emphasizes the scrutiny of content and language, thereby fostering ethical growth alongside literary comprehension.